Potential significance of CX3CR1 dynamics in stress resilience against neuronal disorders - Koichi Inoue (Neural Regeneration Research, 2022)
Recent findings have implicated inflammatory responses in the central nervous system in a variety of neuropsychiatric and neurodegenerative diseases, and the understanding and control of immunological responses could be a major factor of future therapeutic strategies for neurological disorders. Microglia, derived from myelogenous cells, respond to a number of stimuli and make immune responses, resulting in a prominent role as cells that act on inflammation in the central nervous system. Fractalkine (FKN or CX3CL1) signaling is an important factor that influences the inflammatory response of microglia. The receptor for FKN, CX3CR1, is usually expressed in microglia in the brain, and therefore the inflammatory response of microglia is modified by FKN. Reportedly, FKN often suppresses inflammatory responses in microglia and activation of its receptor may be effective in the treatment of inflammatory neurological disorders. However, it has also been suggested that inflammatory responses facilitated by FKN signaling aggravate neurological disorders. Thus, further studies are still required to resolve the conflicting interpretation of the protective or deleterious contribution of microglial FKN signaling. Yet notably, regulation of FKN signaling has recently been shown to be beneficial in the treatment of human diseases, although not neurological diseases. In addition, a CX3CR1 inhibitor has been developed and successfully tested in animal models, and it is expected to be in human clinical trials in the future. In this review, I describe the potential therapeutic consideration of microglial CX3CR1 dynamics through altered FKN signaling.